Teachers Use Code switching In The Classroom - Lalu Agung Rahmat Salehuddin (SOLID, 2019)
This paper discusses about the issues of code switching in the classroom that is used by teachers and students. Code switching that was used by both teachers and students influenced the teaching learning process. The paper also talks about the function of using the code switching in the classroom, how necessary the code switching is and to find out the advantages and the weaknesses of the use of code switching.